1997
DOI: 10.1007/s004310050686
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological features of sudden infant death after a German intervention campaign in 1992

Abstract: Despite intervention campaigns, complete covering of the baby, prone position and heavy maternal smoking are still major risk factors for cot death. Except for sleeping on cushions, all major epidemiological risk factors for cot death act independently. Despite encouraging success in the reduction of risk factors for cot death, there is still substantial need for future endeavours towards a further reduction of modifiable risk factors for SID.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0
7

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 28 publications
2
43
0
7
Order By: Relevance
“…5,11,15 The summary univariable estimate for the 3 studies was 0.38 (95% CI: 0.27-0.54; I 2 ϭ 78%). Because only 2 of the studies provided multivariable ORs, 5,11 meta-analysis to obtain a summary multivariable estimate was not performed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5,11,15 The summary univariable estimate for the 3 studies was 0.38 (95% CI: 0.27-0.54; I 2 ϭ 78%). Because only 2 of the studies provided multivariable ORs, 5,11 meta-analysis to obtain a summary multivariable estimate was not performed.…”
Section: Resultsmentioning
confidence: 99%
“…Two reviewers (Dr Hauck and Ms Tanabe) reviewed all pulled articles for inclusion and for overlapping data. Twenty-four original case-control studies that provided data on the relationship between breastfeeding and SIDS risk 2,[5][6][7][8][9][10][11][14][15][16][17][18][19][24][25][26][27][28][29][30][31][32][33] were identified. Two teams of 2 reviewers independently evaluated 12 studies each according to preset criteria; in cases of disagreement, a third reviewer evaluated the study, and a consensus opinion was reached.…”
Section: Data Sources and Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of SIDS in most areas of Europe is ϳ0.5 to 2 cases per 1000 live births, 1 with notable decreases in the past decade, probably because of campaigns to reduce the rates of deaths associated with risky sleeping conditions. [2][3][4][5][6][7] Although a number of biologic and epidemiologic risk factors, such as prone position, hyperthermia, nicotine abuse during pregnancy, and covering of the head, have been identified, [8][9][10] their interactions and the detailed pathophysiologic mechanisms are still not well understood. 11,12 We 13 and others 14,15 previously noted an association between epidemic pertussis and sudden unexpected deaths among infants.…”
mentioning
confidence: 99%
“…We examined 17 observational studies (Table 1) and found that breastfeeding was reported to have provided a protective effect on SIDS in ten studies 6, 7, 8, 9, 10, 11, 12, 13, 14, 15. No protective effects were found in the other seven 4, 16, 17, 18, 19, 20, 21.…”
Section: Resultsmentioning
confidence: 99%